PERHITUNGAN PERKIRAAN BIAYA PENDIDIKAN ANAK - Farah Kristiani (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
The education of children is a very important investment for the future of children. The preparation of educational funds adapted to the educational plans of the child, their needs and financial capacity of their family. In planning, It is necessary to calculate the estimation of the magnitude of this education fund. This is not easy to do considering the calculation involves the assumptions of the future and also the formulas to calculate the present value of the fund in the future. Besides, it should also be calculated the amount of annual funding, which must be collected to cover their needs. To facilitate the calculation, the program will be made by using MATLAB software. The variable will be filled with the assumption using the current cost information of education. A few illustrations will be provided to help understand the problems that often occur in planning the educational costs for children.